2012
DOI: 10.1590/s0102-09352012000500023
|View full text |Cite
|
Sign up to set email alerts
|

Silagem de híbridos de sorgo associado a percentagens de concentrado no desempenho de novilhos

Abstract: Silagem de híbridos de sorgo associado a percentagens de concentrado no desempenho de novilhos RESUMOAvaliou-se o desempenho de novilhos alimentados em confinamento com silagem de híbridos de sorgo forrageiro e de duplo propósito associado a níveis de concentrado. Foram utilizados 60 novilhos, com idade inicial de 20 meses e peso corporal inicial de 322,45±5,58kg, distribuídos inteiramente ao acaso, nos seguintes tratamentos: três porcentagens de concentrado e dois tipos de silagem de sorgo. Foi verificada int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 15 publications
1
3
1
4
Order By: Relevance
“…This result differs from those obtained by other authors, who found that this variable frequently exhibited quadratic variation -with highest point for diets with 33% bulky material -and linear reduction, or remained constant as the proportion of silage in the diets increased (Missio et al, 2009;Restle et al, 2012). According to Restle et al (2012), although there is no consensus, dry matter intake tends to increase when the content of forage in the diets is greater than that of the concentrate; however, when the concentrate fraction exceeds the forage fraction, dry matter intake tends to reach the inflection point of the curve, decreasing because digestible energy intake is increased and the energy demands of the animals are met.…”
Section: Resultscontrasting
confidence: 93%
See 2 more Smart Citations
“…This result differs from those obtained by other authors, who found that this variable frequently exhibited quadratic variation -with highest point for diets with 33% bulky material -and linear reduction, or remained constant as the proportion of silage in the diets increased (Missio et al, 2009;Restle et al, 2012). According to Restle et al (2012), although there is no consensus, dry matter intake tends to increase when the content of forage in the diets is greater than that of the concentrate; however, when the concentrate fraction exceeds the forage fraction, dry matter intake tends to reach the inflection point of the curve, decreasing because digestible energy intake is increased and the energy demands of the animals are met.…”
Section: Resultscontrasting
confidence: 93%
“…According to Roma Júnior et al (2008), the superior feed conversion found in dairy crossbred bulls is a consequence of the heterosis resulting from crossing zebu and taurine breeds. However, the similar feed conversions for the different proportions of 'Mulato II' grass silage observed in the present study were not reported by Restle et al (2012). These authors explain that the reduction of feed conversion in response to increased silage proportions is due to the reduced energy content in the diets, which leads to greater food intake in order to meet the demands related to weight gain.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…2 Low sugarcane: 380 g kg -1 of sugarcane in the diets with 420 or 620 g kg -1 of BMB in the concentrate (dry matter basis). Restle et al (2012), when the roughage is of medium to low quality, but the energy level of the diets is not a limiting factor, DM intake tends to remain constant with the concentrate increase, which makes the results consistent. The higher crude protein intake obtained with the diets with the higher proportion of sugarcane can be attributed to animal selectivity.…”
Section: Discussionmentioning
confidence: 70%
“…The reduction in DMI with the elevation in dietary density is well documented in the literature (KREHBIEL et al, 2006). However, it should be noted that, according to Restle et al (2012), DMI tends to increase with the inclusion of concentrate in the diet, while the proportion of silage (medium to high quality) is higher than that of concentrate. However, when the fraction of concentrate is higher than that of forage, according to these researchers, DMI tends to approach the inflection point of the curve, from which it decreases as result of the digestible energy intake and attendance of physiological energy of the animal.…”
Section: Resultsmentioning
confidence: 87%